2022
DOI: 10.1210/clinem/dgac685
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preoperative Hyponatremia With Surgical Outcomes: A Systematic Review and Meta-analysis of 32 Observational Studies

Abstract: Background Preoperative hyponatremia is prevalent in patients undergoing surgical procedures, but it is uncertain if hyponatremia will lead to increased risk of surgical mortality and morbidity. Methods A systematic search of Medline (PubMed), Embase and Cochrane Library from inception till 2 July 2021 was performed. Full length articles that reported on the association between surgical outcomes among adults ≥18 years with do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Furthermore, this study showed an increase in several adverse outcomes with thiazide use, in concordance with several previous studies that reported an association of hyponatremia with poor clinical outcomes 24–27 . The in‐depth analyzes such as multivariate analysis were not performed about other outcomes other than the occurrence of hyponatremia, so that a causal relationship could not be claimed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, this study showed an increase in several adverse outcomes with thiazide use, in concordance with several previous studies that reported an association of hyponatremia with poor clinical outcomes 24–27 . The in‐depth analyzes such as multivariate analysis were not performed about other outcomes other than the occurrence of hyponatremia, so that a causal relationship could not be claimed.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, this study showed an increase in several adverse outcomes with thiazide use, in concordance with several previous studies that reported an association of hyponatremia with poor clinical outcomes. [24][25][26][27] The in-depth analyzes such as multivariate analysis…”
Section: Discussionmentioning
confidence: 99%